The Mapping of Shen Congwen in Characters of the Western Hunan world under the Perspective of Identity in the 1930s - Deng, Tianyin (Transactions on Social Science, Education and Humanities Research, 2024)
The 1930s was an important turning point in the history of China's development, and the turbulence of the times also affected the spiritual world of intellectuals. Amidst the literary world of different schools of thought, Shen Congwen, with his unique identity, constructed a world of Western Hunan blending local customs and cultural atmosphere. In the 1930s, Shen Congwen, on the one hand, held fast to his self-identity as a countryman by virtue of his bloodline rooted in the countryside, and on the other hand, his life experience of moving from the countryside to the city enabled him to gain the identity of a "marginal man" in the society. While hovering between the urban and rural areas ,this led Shen to create a lot of far-reaching, complex and diversified characters in the western Hunan world. This process also reveals the impact of the formation of the Dual urban-rural structure on the author.